Intranasal delivery of Huperzine A to the brain using lactoferrin-conjugated N-trimethylated chitosan surface-modified PLGA nanoparticles for treatment of Alzheimer’s disease - Meng QQ (Dove Medical Press, 2018)
Qingqing Meng,1,* Aiping Wang,1,2,* Hongchen Hua,1 Ying Jiang,1 Yiyun Wang,1 Hongjie Mu,1 Zimei Wu,1 Kaoxiang Sun1 1School of Pharmacy, Collaborative Innovation Center of Advanced Drug Delivery System and Biotech Drugs in Universities of Shandong, Yantai University, Yantai, People’s Republic of China; 2State Key Laboratory of Long-Acting and Targeting Drug Delivery System, Shandong Luye Pharmaceutical Co., Ltd, Yantai, People’s Republic of China *These authors contributed equally to this work Background: Safe and effective delivery of therapeutic drugs to the brain is important for successful therapy of Alzheimer’s disease (AD).Purpose: To develop Huperzine A (HupA)-loaded, mucoadhesive and targeted polylactide-co-glycoside (PLGA) nanoparticles (NPs) with surface modification by lactoferrin (Lf)-conjugated N-trimethylated chitosan (TMC) (HupA Lf-TMC NPs) for efficient intranasal delivery of HupA to the brain for AD treatment.Methods: HupA Lf-TMC NPs were prepared using the emulsion–solvent evaporation method and optimized using the Box–Behnken design. The particle size, zeta potential, drug entrapment efficiency, adhesion and in vitro release behavior were investigated. The cellular uptake was investigated by fluorescence microscopy and flow cytometry. MTT assay was used to evaluate the cytotoxicity of the NPs. In vivo imaging system was used to investigate brain targeting effect of NPs after intranasal administration. The biodistribution of Hup-A NPs after intranasal administration was determined by liquid chromatography–tandem mass spectrometry.Results: Optimized HupA Lf-TMC NPs had a particle size of 153.2±13.7 nm, polydispersity index of 0.229±0.078, zeta potential of +35.6±5.2 mV, drug entrapment efficiency of 73.8%±5.7%, and sustained release in vitro over a 48 h period. Adsorption of mucin onto Lf-TMC NPs was 86.9%±1.8%, which was significantly higher than that onto PLGA NPs (32.1%±2.5%). HupA Lf-TMC NPs showed lower toxicity in the 16HBE cell line compared with HupA solution. Qualitative and quantitative cellular uptake experiments indicated that accumulation of Lf-TMC NPs was higher than nontargeted analogs in 16HBE and SH-SY5Y cells. In vivo imaging results showed that Lf-TMC NPs exhibited a higher fluorescence intensity in the brain and a longer residence time than nontargeted NPs. After intranasal administration, Lf-TMC NPs facilitated the distribution of HupA in the brain, and the values of the drug targeting index in the mouse olfactory bulb, cerebrum (with hippocampus removal), cerebellum, and hippocampus were about 2.0, 1.6, 1.9, and 1.9, respectively.Conclusion: Lf-TMC NPs have good sustained-release effect, adhesion and targeting ability, and have a broad application prospect as a nasal drug delivery carrier. Keywords: Huperzine A, lactoferrin, N-trimethyl chitosan, nose-to-brain, nanoparticles, Alzheimer’s disease